Mallard, Grégoire. 2019. Gift Exchange: Book Review - Snikersproge, Ieva (Swiss Journal of Sociocultural Anthropology, 2021)
Mallard, Grégoire. 2019. Gift Exchange: The Transnational History of a Political Idea. Cambridge: Cambridge University Press. ISBN: 978-1108453486. 280 p.